The Home Market Shadow - Jens Suedekum (Institute for the Study of Labor (IZA), 2005)
The home market effect (HME) is a distinguishing feature of the ?new? theory of international trade, but it is uncertain whether this effect survives if one moves beyond the simplifying setup with only two countries. We present a three -country version of the seminal model by Krugman (1980) and analyse under which circumstances the HME is present once third country effects are taken into account. We show that an exogenous increase in the home country?s expenditure level on the modern good will unambiguously lead to an overproportional output reaction. If production in the foreign world shifts from a more remote to a better accessible economy, industry location in the home country is negatively affected. Thus, if the expenditure increase is small relative to the foreign expenditure shifting, an under-proportion al output reaction in the home country can result. In a more extreme case the industry share of the home country can even decrease. This phenomenon is labelled the ?home market shadow?.
Keywords: F14; F12; R12; 330; new trade theory; home market effect; hub effect; Neue Aussenhandelstheorie; Terms of Trade; Mehr-Sektoren-Modell; Mehr-Länder-Modell; Marktanteil; Theorie